ASSESSING RELATIONSHIPS BETWEEN LAND USE CHANGES AND THE DEVELOPMENT OF A ROAD NETWORK IN THE HODONÍN REGION (CZECH REPUBLIC) - Jedlička, Jiří; Havlíček, Marek; Dostál, Ivo; Huzlík, Jiří; Skokanová, Hana (Quaestiones Geographicae, 2019)
The paper assesses the development of land use and a road network from 1836 to 2016 in the Hodonín region (Czech Republic). The aim of the article is to verify relationship between the road construction and land use changes in their vicinity. The intensity of land use change processes between adjacent periods was calculated at various distances from roads. ESRI’s geographic information systems and geostatistics were used. This helped in assessing significance of impact of road vicinity on land use changes. The time interval of periods for comparison varied between 25 and 80 years due to availability of historical sources. In each period about 20% of the region was affected by land use changes. After the roads were built, there was an increase in the intensity of land use changes in their vicinity. It has been proofed that presence of a road can be considered one of the driving forces of long-term land use changes in this region. This so-called technological driving force impacted mainly urbanisation and other anthropogenic processes, agricultural intensification and grassing. Its significance is gradually increasing due to urbanisation, industrialisation, motorization and the rising mobility. Our results from the Hodonín region indicate that urbanisation and other anthropogenic processes have the closest relationship with the distance from major roads.